'Evaluation of the introduction of a dental virtual simulator on the performance of undergraduate dental students in the pre‐clinical operative dentistry course'. (16th January 2020) - Murbay, Sukhdeep; Neelakantan, Prasanna; Chang, Jeffrey Wen Wei; Yeung, Shadow
Abstract: Introduction: Virtual reality‐based platforms are becoming increasingly popular in education. The aim of this study was to evaluate the performance of undergraduate dental students with the introduction of the Moog Simodont dental trainer (VR) within the pre‐clinical curriculum in the direct restoration module of the operative dentistry course using manual and digital methods. Methods: Thirty‐two randomly selected year 2 undergraduate students were divided into two groups: group 1, exposed to the Moog Simodont dental trainer (VR) and group 2, no exposure to VR. All students were then evaluated in carrying out a Class I preparation in a single‐blinded fashion. All preparations were evaluated by three assessors using a traditional manual approach and a digital software. Statistical analysis of the data was performed using chi‐square test (alpha = 0.05). Results: The number of students who performed satisfactory preparations was more in group 1 (12/16), compared to group 2 (7/16). The percentage of satisfactory domains was significantly higher in group 1, compared to group 2, both in the manual evaluation (83.9% (94/112) and 59.8% (67/112) in groups 1 and 2, respectively) and in the digital evaluation (85.7% (96/112) and 55.4% (62/112) in groups 1 and 2, respectively) ( P < .05). There was no significant difference between the manual and digital methods of evaluation with regard to the percentage of satisfactory or unsatisfactory preparations ( P > .05). Conclusions: The use of the Moog Simodont dental trainer (VR) significantly improved the satisfactory performance of students. The virtual reality simulator may be a valuable adjunct in the undergraduate direct restorations course and for remedial student.